THEMATHIC LEARNING MODEL AND ITS EFFECT ON STUDENTS’ LEARNING MOTIVATION (Case Study at Nature Elementary School of Baturraden) - Safinatun Najah; Ngatman Ngatman; Moh Salimi (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The purpose of this study is to describe the implementation of thematic learning model and its impact on the students’ learning motivation of  nature elementary school of Baturraden. This research is case study research. Subjects in this study were students, teachers, and parents of grade IV and V SD Alam Baturraden. The result of the research shows that the implementation of thematic teaching model in SD Alam Baturraden has an impact on learning motivation which is characterized by the appearance of the characteristics of children who have high learning motivation, namely: (1) students are diligent in doing the task; (2) resilient in the face of adversity; (3) shows interest in the problem; (4) independent, (5) creative; (6) strong opinion, (7) happy to find and solve problems.